PENGARUH REVITALISASI FASILITAS WISATA DAN AKSESIBILITAS TERHADAP KEPUTUSAN BERKUNJUNG DI TAMAN MINI INDONESIA INDAH - Wanda Junia Ningrum; Wasino (LPPM Universitas Asa Indonesia, 2025)
The purpose of this study is to determine the effect of revitalization of tourist facilities and accessibility at Taman Mini Indonesia Indah. This study uses a quantitative method. The sampling technique uses the Accidential Sampling Technique for tourists. The data collection technique used in this study is a questionnaire and observation. Data were obtained from 100 respondents/sample selected through non-probability sampling/incidental sampling techniques, namely research techniques based on accidentally meeting researchers during data collection. The results of the study indicate that the Revitalization Variable has a positive and significant effect on the decision to visit Taman Mini Indonesia Indah. This can be seen from the significance of the F Calculate value > F Table or 58.453 > 11.283 and the significance level is 0.001 < 0.05 so is rejected and is accepted, it can be concluded that the Revitalization, Tourist Facilities, and Accessibility variables simultaneously have a significant effect on the decision to visit Taman Mini Indonesia Indah.